EVOLUTION AND VARIATION OF THE SPANISH LANGUAGE IN LATIN AMERICA - Nodira Kholikulova Turdikulovna (Western European Studies, 2024)
This article explores the evolution of the Spanish language in Latin America, emphasizing its historical, cultural, and linguistic development. The author highlights the significant influence of indigenous languages, cultural exchanges, and colonization on shaping regional dialects and variants. It is acknowledged that Latin American Spanish evolved as a result of the adaptation of Castilian Spanish to diverse geographical and social conditions, resulting in a linguistic phenomenon rich in variation and distinctiveness. Furthermore, the study delves into the contributions of prominent linguists who documented and analyzed the linguistic evolution of the region.
Keywords: Spanish language evolution; Latin American Spanish; regional dialects